ANALYSIS AND DESIGN OF IT PROCUREMENT COMPANY ENTERPRISE ARCHITECTURE USING TOGAF ARCHITECTURE DEVELOPMENT METHOD (CASE STUDY: PT MITRA TELEMATIKA UTAMA) - M Alvie Helmuzar; Rahmat Yasirandi; Rio Guntur Utomo (STKIP PGRI Tulungagung, 2022)
Business processes in the business world require companies to be able to manage information properly and the information needs of each interested party can be met quickly and accurately. The development of EA (Enterprise Architecture) in the company is a complex and challenging job. PT Mitra Telematika Utama has problems with accounting activities and bookkeeping activities. Planning the organizational information system architecture is a complex process, so the planning process must be managed with clear guidelines that aim to align the organization's business technology and public strategy to create maximum results for the organization. Designing an enterprise architecture model requires a framework to manage complex systems and align business with information technology that will be developed within the organization. TOGAF is a framework developed by The Open Group from 1995 to the present. TOGAF provides methods and tools used in planning, creating, designing, and managing the development and implementation of enterprise architecture. TOGAF provides a detailed method on how to build and manage and implement enterprise architecture and information systems called ADM (Architecture Development Method). TOGAF provides methods and tools used in planning, creating, designing, and managing the development and implementation of enterprise architecture. TOGAF provides a detailed method on how to build and manage and implement enterprise architecture and information systems called ADM (Architecture Development Method). TOGAF provides methods and tools used in planning, creating, designing, and managing the development and implementation of enterprise architecture. TOGAF provides a detailed method on how to build and manage and implement enterprise architecture and information systems called ADM (Architecture Development Method). So in planning the enterprise architecture, TOGAF ADM produces application architecture blueprints, business architectures, technology architectures, data architectures, and implementation roadmaps where these blueprints are useful as a reference when developing an enterprise architecture in this case at PT. Mitra Telematika Utama.